Distance Education: The Satisfaction Level of Science and Mathematics Teachers towards the Electronic Educational Supervision - Ali Khaled Bawaneh; Belal Sadiq Rababh; Subreen Mahmoud Al-Salman (Ilmu Inovasi Nusantara, 2023)
The study aimed to assess the satisfaction of Jordanian science and mathematics teachers with electronic educational supervision and its correlation with their interactions with educational supervisors. The research encompassed all science and mathematics teachers in Jordan, both genders, across public and private schools in the Irbid Governorate. The study's sample comprised 184 male and female teachers. Data collection involved a meticulously validated and reliable questionnaire disseminated electronically through the snowball method. Statistical analyses, including means, standard deviations, frequencies, percentages, and one-way analysis of variance (ANOVA), were employed to address the research questions. The findings revealed that Jordanian science and mathematics teachers, on average, reported a moderate satisfaction level with electronic supervision and their associations with educational supervisors. Statistically significant differences were observed in satisfaction levels based on school type, favoring private institutions. However, no significant variations emerged concerning other factors like gender, years of experience, and technical skills possession. Consequently, the study proposed several recommendations: fostering the culture of electronic supervision, incorporating distance education as a viable alternative, or integrating it gradually into courses annually. It emphasized the need for comprehensive training in educational technology for teachers and supervisors to enhance their value addition. Infrastructure readiness, including equipment and high-speed internet, was underscored for effective implementation. The study advocated for ongoing research to address challenges and optimize e-learning and supervision methodologies. Ultimately, the goal is to ensure a seamless integration of technology into education, thereby improving overall satisfaction and efficacy in the learning environment